Two sibling species of Leiopus Audinet-Serville, 1835 (Coleoptera: Cerambycidae) from Europe: L. nebulosus (Linnaeus, 1758) and L. linnei sp. nov. - Wallin, Henrik; Nylander, Ulf; Kvamme, Torstein (Zootaxa, 2009)
The common European cerambycid Leiopus nebulosus (Linnaeus, 1758) is herein split into two sibling species. The male genitalia characters, as well as spermathecae in females, were examined and found to provide strong support for this separation. A new species, Leiopus linnei sp. nov., is based on specimens mainly from Scandinavia. The establishment of the new species is supported by DNA barcoding of Scandinavian specimens of L. nebulosus, L. linnei sp. nov., and L. punctulatus (Paykull, 1800). There are significant genetic differences between all these species. The geographical distribution and the bionomy of L. nebulosus and L. linnei sp. nov. are described. The type of Cerambyx nebulosus Linnaeus, 1758 is lost. A neotype of Cerambyx nebulosus, currently Leiopus nebulosus (Linnaeus, 1758), is designated and a redescription of L. nebulosus is presented. A key for the identification of L. nebulosus and L. linnei sp. nov. is provided. The varieties L. nebulosus var. dissimilis Pic, 1889, L. nebulosus var. unifasciatus Pic, 1891, and L. nebulosus var. siculus Pic, 1924 are considered as junior synonyms, syn.nov. of L. nebulosus.